فاعلية برنامج إرشادي لتنمية وعي مقدمي الرعاية الأسرية لمرضى الزهايمر في مدينة الرياض: دراسة شبة تجريبية - ابن خميس، مودة بنت عبدالمحسن (المركز الوطني للدراسات والبحوث الاجتماعية, 2023)
هدفت الدراسة إلى التعرف على فاعلية برنامج إرشادي في تنمية وعي مقدمي الرعاية الأسرية لمرضى الزهايمر في مدينة الرياض، وتكونت عينة الدراسة الأساسية (۳۱) من أسر مقدمي الرعاية لمرضى الزهايمر ممن تنطبق عليهم شروط العينة، واعتمدت الدراسة على المنهج شبه التجريبي، ولتحقيق أهداف الدراسة استخدمت الباحثة من إعدادها المقياس القبلي والبعدي لقياس مدى وعي مقدمي الرعاية الأسرية لمرضى الزهايمر، وتم تطبيق البرنامج الإرشادي المكون من (۱۲) جلسة إرشادية، بواقع (۳) جلسات كل أسبوع، مدة كل جلسة (٤٥) دقيقة. وأظهرت الدراسة النتائج الآتية: - وجود فروق معنوية ذات دلالة إحصائية عند مستوى الدلالة المعنوية (۰٫۰۱) بين متوسطات القياسين القبلي والبعدي للمجموعة التجريبية من مقدمي الرعاية الأسرية لمرضى الزهايمر من الناحية الاجتماعية الصالح القياس البعدي. - وجود فروق معنوية ذات دلالة إحصائية عند مستوى الدلالة المعنوية (۰٫۰۱) بين متوسطات القياسين القبلي والبعدي للمجموعة التجريبية من مقدمي الرعاية الأسرية لمرضى الزهايمر من الناحية النفسية لصالح القياس البعدي. - وجود فروق معنوية ذات دلالة إحصائية عند مستوى الدلالة المعنوية (۰٫۰۱) بين متوسطات القياس القبلي والقياس البعدي، للمجموعة التجريبية من مقدمي الرعاية الأسرية لمرضى الزهايمر من الناحية الصحية لصالح القياس البعدي. The study aimed to recognize the effectiveness of an indicative program to develop the awareness of family caregivers for Alzheimer's ptients in Riyadh. The sample of the main study consisted of (31) family caregivers for Alzheimer's patients, who meet the conditions were chosen in this sample. This study relied on the semi-experimental approach and for achieving the objectives of the study, the researcher prepared a pre and post scale to measure the level of awareness of family caregivers for Alzheimer's patients. Also, the indicative program that consists of (12) counseling sessions, at a rate of (3) sessions per week, the duration of each session (45) min. The results of the study: morale - There are statistically significant differences at the level of the moral significance (0.01) between the average of the pre- and post-measurement for the experimental group of family caregivers for Alzheimer's patients from a social point of view, for the post-measurement. - There are statistically significant differences at the level of the moral significance (0.01) between the means of the pre- and post-measurement for the experimental group of family caregivers for Alzheimer's patients from a psychological point of view, for the post- measurement. - There are statistically significant differences at the level of the moral significance (0.01) between the averages of the pre- and post-measurement, for the experimental group of family caregivers for Alzheimer's patients from the health side, for the post-measurement.
Keywords: الخدمة الاجتماعية -- الرعاية الأسرية -- مرضى الزهايمر -- السعودية